Analisis Implikasi Penerapan Bi’ah Lughawiyyah pada Lembaga Kursus Bahasa Arab Naatiq Internasional Arabiyyah - Azmy, Muhammad Ulul (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
This study aims to analyze the implementation of bi'ah lughawiyyah and its implications for the acquisition of Arabic by participants at the Naatiq International Arabic Language and Literature Course Institute. This study uses a qualitative approach with a descriptive-analytical research type. Data collection techniques include observation, in-depth interviews, and documentation, with the main informants consisting of the founder and tutor as well as course participants. Data analysis is carried out through data reduction, data presentation, and conclusion drawing, and its validity is tested through source and technique triangulation. The results of the study show that the linguistic environment in the institution is implemented systematically through the integration of institutional character, learning programs, language rules, periodic evaluations, and the role of tutors as linguistic models. The implementation of an Arabic language environment has proven to have a positive impact on improving participants' Arabic language competence, particularly speaking skills, and contributes to the formation of self-confidence and positive affective attitudes. In addition, language habits and discipline play a role in shaping participants' linguistic habits on an ongoing basis. However, this study also found a number of challenges, such as differences in participants' backgrounds, abilities, and levels of motivation, which require adaptive pedagogical management. This study confirms that bi'ah lughawiyyah is not merely a local institutional tradition, but rather a pedagogical approach with a strong theoretical foundation in the acquisition of Arabic as a second language. The findings of this study are expected to contribute to the development of Arabic language learning, particularly in the design of an effective and sustainable language environment.